Analisis Risiko Ketulian Pekerja Pemotong Rumput yang Terpapar Kebisingan di PT. Pertamina (Persero) Marketing Operation Region V Terminal Bahan Bakar Minyak Tanjung Wangi - Olga Febriana Safitrie; Abdul Rohim Tualeka (Universitas Airlangga, 2023)
Introductions: Lawn mow worker was at risk of deafness due to noise because the lawn mow worker was carried on the back. Continuous noise exposured can increase the risk of hearing loss. Objectives: The purposed of this study was to analyze the risk of deafness in lawn mower worker who were exposed to noise at PT. Pertamina (Persero) Marketing Operation Region V Terminal Bahan Bakar Minyak Tanjungwangi. Methods: This research is a quantitative study using a cross-sectional approach, furthermore the research is conducted at one time. Sampling used a total sampling technique with a total sample of 10 people as the unexposed group and 10 people as the exposed group. Retrieval of research data obtained by measuring environmental noise, measuring the threshold value of workers and questionnaires. As well as observing the work environment by researchers. Furthermore, data analysis was carried out on the strong relationship between noise and worker age, years of service, and use of Personal Protective Equipment (APT) on hearing status using the Pearson statistical test. Results: The results showed that the average noise intensity received by grass cutter workers was 87.43 dB, and at office locations it was 61.9 dB. The average Hearing Threshold Value of the exposed group in the left ear was 17.5 dB and the right ear was 19,5 dB. As well as in the unexposed group, the left ear was 21 dB and the right ear was 20.75 dB. Conclussion: Noise, age, years of service, and use of ear protection devices have a relationship to the hearing status of workers. Based on statistical tests, it showed that the value of p> 0.005, and then noise had a weak relationship with age, years of service and use of ear protection devices. The advice given to PT. Pertamina (Persero) TBBM Tanjungwangi is to supervise the use of ear protection devices for workers so as to reduce the risk of workers' deafness due to exposure to lawn mowers